Gender norms and family planning decision-making in Tanzania: a qualitative study - Sidney R. Schuler; Elisabeth Rottach; Peninah Mukiri (AOSIS, 2011)
Experience suggests that the incorporation of gender approaches into family planning (FP) and reproductive health (RH) programs may increase their impact and sustainability, but further work is needed to examine the interactions between gender norms and family planning and to incorporate this understanding into behavior change communication (BCC) in specific social contexts. We conducted open-ended, in-depth interviews with 30 young currently married men, 30 young married women and 12 older people who influenced FP decisions. Six focus group interviews were also conducted. The interviews focused on the role of gender norms in reproductive decision-making and contraceptive use among young married men and women in Tanzania. The findings suggest that gender factors, such as men's dominance in decision-making do function as barriers to the use of modern contraceptives, but that fear of side effects, by both men and women, may be even more important deterrents. Results from this research will inform the development of BCC interventions to be tested in a subsequent intervention study in which gender factors and poor information about contraceptive methods will be addressed.